Lost or Forgotten: The nuclear cathepsin protein isoforms in cancer. (10th October 2019) - Soond, Surinder M.; Kozhevnikova, Maria V.; Frolova, Anastasia S.; Savvateeva, Lyudmila V.; Plotnikov, Egor Y.; Townsend, Paul A.; Han, Yuan-Ping; Zamyatnin, Andrey A.
Abstract: While research into the role of cathepsins has been progressing at an exponential pace over the years, research into their respective isoform proteins has been less frenetic. In view of the functional and biological potential of such protein isoforms in model systems for cancer during their initial discovery, much later they have offered a new direction in the field of cathepsin basic and applied research. Consequently, the analysis of such isoforms has laid strong foundations in revealing other important regulatory aspects of the cathepsin proteins in general. In this review article, we address these key aspects of cathepsin isoform proteins, with particular emphasis on how they have shaped what is now known in the context of nuclear cathepsin localization and what potential these hold as nuclear-based therapeutic targets in cancer. Highlights: Recently, full-length cathepsin proteins have been shown to locate to the nucleus. They have been shown to modulate cell gene transcription and proliferation. We review the literature to highlight the origins of this important observation. We also highlight molecular mechanisms that have been proposed. We propose similar mechanisms for nuclear cathepsin isoform proteins need defining. We also highlight the importance of defining their nuclear function.